DYNAMICS OF MEASLES INCIDENCE AMONG CHILDREN AND ASSESSMENT OF THE IMPACT OF IMMUNIZATION STRATEGIES ON DISEASE PREVENTION - Samadaliyev N. N. (Innovate Conferences, 2025)
Measles remains one of the most contagious viral diseases, primarily affecting children and continuing to pose a significant global public health challenge. Despite the availability of an effective and safe vaccine, periodic outbreaks persist in both developing and developed countries, reflecting existing gaps in immunization coverage and the uneven distribution of herd immunity. According to the World Health Organization (WHO), more than 136,000 measles-related deaths were recorded globally in recent years, most of which occurred among unvaccinated children under five years of age.